2022
DOI: 10.1002/lary.30307
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Delay in Human Papillomavirus Negative Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective: Failure to recognize symptoms of non-human papillomavirus-associated oropharyngeal squamous cell carcinoma (HPV(À)OPSCC) at presentation can delay diagnosis and treatment. We aim to identify patient factors and provider practice patterns that delay presentation and care in HPV(À)OPSCC.Methods: Retrospective review at a tertiary care center. Patients with HPV(À)OPSCC receiving treatment from 2006 to 2016. Patients were excluded if their date of symptom onset or diagnosis was unknown after thorough re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A total of 2830 studies were initially identified for screening, of which 50 were included in the review . Reasons for exclusion are depicted in the Figure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2830 studies were initially identified for screening, of which 50 were included in the review . Reasons for exclusion are depicted in the Figure.…”
Section: Resultsmentioning
confidence: 99%
“…The most studied HNC subsite was laryngeal cancer with 25 studies (50%), followed by oral cavity and oropharynx, each with 19 studies (38%). The most assessed outcome was advanced overall stage at presentation or diagnosis among 37 studies (74%) . Other options included advanced tumor size, advanced nodal disease, metastatic disease at presentation, and delayed diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol use was determined by consumption of > 5 alcoholic beverages per week. 6 To assess factors independently associated with diagnostic delay in this population, a multivariable logistic regression analysis was performed (IBM SPSS Statistics for Windows, IBM Corp., Armonk, NY, USA) using characteristics that were statistically more likely to be present in patients who experienced diagnostic delay versus those who did not.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation by three or more providers or being prescribed analgesia prior to diagnosis was associated with significant delays in diagnosis of nearly a year. 6 Additionally, patients with HPVþ OPSCC who were diagnosed at >12 months from symptom onset were more likely to have T4 disease and higher overall American Joint Committee on Cancer (AJCC) clinical stage at presentation than patients diagnosed < 12 months from symptom onset. 7 The aim of the present study was to further characterize HPVþ OPSCC by assessing for the presence of diagnostic delay compared with HPV-OPSCC and evaluating the role of various management factors that potentially impact time to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation